Sugestywność etycznego przekazu prologów w poemacie Lukrecjusza - Grzelak-Krzymianowska, Adriana (Collectanea Philologica, 2019)
Lucretius, considered to be the continuator of Epicure, is the author of the poem De rerum natura. Essentially, this title suggests that it is a work that addresses the problems of ancient physics, in this case the materialistic concept of reality. Of course, this is true, but besides the physical doctrine, the poem also contains numerous sections on ethics and morality. Although no part of De rerum natura is a constant ethical argument, the whole text is permeated with information that serves precisely this purpose. The aim of this article is to show how the poet uses in his prologues for subsequent books of the poem the structure, content and various stylistic and rhetorical elements to convince the reader of the rightness and values of the explicitly and implicitly demonstrated ethical views he proclaims.